Gravitational rainbow - Accioly, Antonio [UNESP]; Bias, Harold [UNESP] (American Physical Society (APS), 2001)
It is shown that, unlike Einstein's gravity, quadratic gravity produces dispersive photon propagation. The energy-dependent contribution to the deflection of photons passing by the Sun is computed and subsequently the angle at which the visible spectrum would be spread over is plotted as a function of the Rμν2-sector mass. © 2001 The American Physical Society.